Students’ Difficulties in Translating Texts from English to Indonesian and Their Causes - Vira Agustin; Witri Oktavia (Journal of English Language Teaching, 2023)
This study aims to learn and understand the difficulties faced by Universitas Negeri Padang's sixth-semester students who are translating texts from English to Indonesian. The qualitative descriptive research design is used in this study. Guidelines for the test and interview were used to get the data. The participants in this study were chosen by the researcher using cluster random sampling. Participants in this study included 20 sixth-semester English Education students at Universitas Negeri Padang who had taken a translation course and were enrolled for the 2019–2020 academic year. This research result shows that the most common difficulties that faced by students is grammatical meaning with 44,5%. In linguistic factor, 80% or 8 of 10 students felt difficult in translating text. The struggles of the students were caused by a variety of circumstances. The significance of the source text was difficult for the students to comprehend. As a result, it is difficult for them to translate it into the intended text. The finding is that linguistic issues contributed more to the students' difficulties than non-linguistic ones.